Integrating Client Tracker Tool Into Fistula Management: Experience From the Fistula Care Plus Project in the Democratic Republic of Congo, 2017 to 2019 - Justin Paluku; Esther Kitambala; Cathy Mufungizi Furaha; Rita Bulu Bobina; Pascal Habamungu; Bienvenu Salim Camara; Bienvenu Salim Camara; Sidikiba Sidibe; Don Félicien Banze Kyongolwa; Vandana Tripathi; Alexandre Delamou; Alexandre Delamou (Frontiers Media S.A., 2022)
This study aimed to document the experience of integration and the contribution of the Client Tracker (CT) to female genital fistula (FGF) management and data quality in sites supported by the Fistula Care+ Project in the Democratic Republic of Congo (DRC), from 2017 to 2019. It was a parallel mixed methods study using routine quantitative data and qualitative data from in-depth interviews with the project staff. Quantitative findings indicated that CT forms were present in the medical records of 63% of patients; of these, 38% were completely filled out, and 29% were correctly filled out. Qualitative findings suggested that the level of use of CT in the management of FGF was associated with staff familiarity with the CT, staff understanding of concepts in the CT forms, and the CT-related additional workload. The CT has mainly contributed to improving data quality and reporting, quality of care, follow-up of fistula patients, and self-supervision of management activities. A possible simplification of the CT and/or harmonization of its content with existing routine forms, coupled with adequate continuous training of staff on record-keeping, would further contribute to maximizing CT effectiveness and sustainability.